Pengaruh Struktur Modal, Likuiditas, ESG Score, dan Efisiensi Operasional terhadap Kinerja Keuangan Perusahaan - Arva Febryan Noor Rayyani; Kurnia Rina Ariani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to conduct an empirical analysis of how capital structure, liquidity, ESG scores, and operational efficiency affect the financial performance of manufacturing firms that are listed on the Indonesia Stock Exchange between 2022 and 2023. Annual and sustainability reports provide supplementary data for the project. Purposive sampling, the approach used for sample selection, yielded a final sample of 36 firms. Using traditional assumption testing in conjunction with multiple linear regression is one method of data analysis. The findings demonstrate that operational efficiency, capital structure, liquidity, and ESG score significantly impair financial performance as determined by Return on Equity (ROE). In order to maintain optimal financial performance, the findings highlight how crucial it is for businesses to properly manage their finance structure, liquidity, and sustainability policies.